MAIN FACTORS OF THE PHYSICAL CAPACITY OF 15–16-YEAR-OLD STUDENTS (AFTER THE COVD-19 PANDEMIC IN THE SCHOOL YEAR 2019/2020) - M. Borukova; M. Kuleva (Trakia Journal of Sciences)
The aim of the study was to reveal the factor structure and to derive the main factors of physical capacity in 15–16-year-old boys after the first period of isolation during the COVID-19 pandemic. This would help optimize the online learning process in physical education and sports during the next school years. 252 students took part in the study. The following research methods were applied for the realization of the research: study of the literature and theoretical analysis of the specialized literature, and sportspedagogical testing. To assess the physical capacity 5 tests were applied: Running 30 m (1), long jump with both feet from place (2), 3 kg medicine ball throwing with both hands from a standing position over the head (3), 200 m running (4) and the Test for Agility and Spatial Coordination (5). The results were processed with SPSS using mathematical and statistical methods: variation analysis, sigma deviation method and factor analysis. CONCLUSIONS: The studied students have average level of physical capacity, compared to the same age group for Bulgarian students. In 15–16-year-old boys the factor structure is composed of 3 main factors, which explain the very high percentage of the initial variance of the studied trend (87.37%). The most important is the first factor, which is related to the explosive force of the lower limbs in horizontal efforts, speed capabilities and the endurance of the examined boys.